PERAN LUMBUNG DESA MODERN DALAM PEMBERDAYAAN EKONOMI RAKYAT - Sutarto, Sutarto (AGRITEXTS: Journal of Agricultural Extension, 2008)
The research is aimed at finding out: the correlation between the farmers ' social and economic factors and the adoption level of technological innovation for the corn commodity in Sidoharjo sub-district, Wonogiri regency; the correlation between the farmers ' assessment on the agricultural extension agents' performance and the adoption level of technological innovation for the corn commodity in Sidoharjo sub-district, Wonogiri regency. The research is a survey one. Population of the research was the farmers who planted corn commodity in Sidoharjo sub-district, Wonogiri regency. Samples of the research were taken by using a random sampling technique. The samples consisted of63 farmers. Data ofthe research were gathered by means of questionnaire. The data were then analyzed by using r product moment formula with the computer program of SPSS 12. 0 for windows. The results ofthe analysis on the variables ofthe farmers' social and economic factors are as follows: (]) there is a significant correlation between the farmers' age and the adoption level of technological innovation; (2) there is a significant correlation between the farmers' education level and the adoption level of technological innovation; (3) there is a significant correlation between the farmers' dimension of land and the adoption level of technological innovation; (4) there is a significant correlation between the farmers' income and the adoption level of technological innovation; (5) there is not any correlation between the farmers ' experience and the adoption level of technological innovation; (6) and there is a significant correlation between the farmers ' social and economic conditions and the adoption level of technological innovation. Based on the results of the analysis, the proposed hypothesis is verified that "there is a significant correlation between the farmers' social and economic factors and the adoption level oftechnological innovation ofthe corn commodity in Sidoharjo sub-district, Wonogiri regency"